2001
DOI: 10.1006/cbir.2000.0584
|View full text |Cite
|
Sign up to set email alerts
|

Local Regulation of Anion Secretion by Pituitary Adenylate Cyclase‐activating Polypeptide in Human Colonic T84 Cells

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a novel hypothalamic peptide, which has been shown to exert various functions in a number of tissues, including exocrine and endocrine tissues. The present study investigated the role of local PACAP in the control of anion secretion by the human colonic T84 cell. Both bioactive forms of PACAP-27 and PACAP-38 gave rise to a dose-dependent increase in the short-circuit current (I(SC)). However, there was a reversal in the order of potency observed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…In conclusion, we have demonstrated that human bronchial Calu‐3 epithelial cells expressed basolateral VPAC 1 receptors which interact with VIP or PACAP‐27 causing activation of CFTR‐mediated chloride secretion via a pathway in which protein kinase A and C are both involved. Our study therefore shows that as in the intestine ( Waldman et al , 1977 ; Chang & Rao, 1991; Nguyen et al , 1992 ; Leung et al , 2001 ; Izu et al , 2002 ) CFTR is an important molecular target for the physiological action of VIP and PACAP‐27 in the chloride transepithelial transport of human bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In conclusion, we have demonstrated that human bronchial Calu‐3 epithelial cells expressed basolateral VPAC 1 receptors which interact with VIP or PACAP‐27 causing activation of CFTR‐mediated chloride secretion via a pathway in which protein kinase A and C are both involved. Our study therefore shows that as in the intestine ( Waldman et al , 1977 ; Chang & Rao, 1991; Nguyen et al , 1992 ; Leung et al , 2001 ; Izu et al , 2002 ) CFTR is an important molecular target for the physiological action of VIP and PACAP‐27 in the chloride transepithelial transport of human bronchial epithelial cells.…”
Section: Discussionmentioning
confidence: 62%
“…In digestive tissues, it is known that VIP/PACAP receptors regulate transepithelial chloride transport ( Waldman et al , 1977 ; Chang & Rao, 1991; Nguyen et al , 1992 ; Leung et al , 2001 ; Izu et al , 2002 ). Therefore, we studied the activity of chloride channels in human airway epithelial Calu‐3 cells in the presence of VIP or PACAP‐27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As PACAP is a cAMP stimulating peptide, it can be assumed that the neuropeptide plays a role endogenously in the aqueous humor production. Furthermore, PACAP and its receptors have also been shown to act on chloride channels, which are essential in the production of aqueous humor, independently from the cAMP pathway (Alshafie et al 2014 ; Derand et al 2004 ; Leung et al 2001 ; Martinez-Rojas et al 2021 ). The role of PACAP has been implied not only in the production, but also in the absorption of the aqueous humor, as our most recent data have provided evidence that PACAP treatment leads to reduced intraocular pressure in a rat model of glaucoma (Szabo et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As PACAP is a cAMP stimulating peptide, it can be assumed that the neuropeptide plays a role endogenously in the aqueous humour production. Furthermore, PACAP and its receptors have also been shown to act on chloride channels, which are essential in the production of aqueous humour, independently from the cAMP pathway (Alsha e et al 2014; Derand et al 2004;Leung et al 2001;Martinez-Rojas et al 2021). The role of PACAP has been implied not only in the production, but also in the absorption of the aqueous humour, as our most recent data have provided evidence that PACAP treatment leads to reduced intraocular pressure in a rat model of glaucoma (Szabo et al 2021).…”
Section: Discussionmentioning
confidence: 99%